Macromolecular Crowding as a Regulator of Gene Transcription - Matsuda, Hiroaki; Putzel, Gregory Garbès; Backman, Vadim; Szleifer, Igal (Biophysical journal, 2014)
Studies of macromolecular crowding have shown its important effects on molecular transport and interactions in living cells. Less clear is the effect of crowding when its influence is incorporated into a complex network of interactions. Here, we explore the effects of crowding in the cell nucleus on a model of gene transcription as a network of reactions involving transcription factors, RNA polymerases, and DNA binding sites for these proteins. The novelty of our approach is that we determine the effects of crowding on the rates of these reactions using Brownian dynamics and Monte Carlo simulations, allowing us to integrate molecular-scale information, such as the shapes and sizes of each molecular species, into the rate equations of the model. The steady-state cytoplasmic mRNA concentration shows several regimes with qualitatively different dependences on the volume fraction, ϕ, of crowding agents in the nucleus, including a broad range of parameter values where it depends nonmonotonically on ϕ, with maximum mRNA production occurring at a physiologically relevant value. The extent of this crowding dependence can be modulated by a variety of means, suggesting that the transcriptional output of a gene can be regulated jointly by the local level of macromolecular crowding in the nucleus, together with the local concentrations of polymerases and DNA-binding proteins, as well as other properties of the gene’s physical environment.